2015
DOI: 10.1002/ajmg.c.31434
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, assessment, and management of adults with joint hypermobility syndrome/Ehlers–Danlos syndrome hypermobility type among flemish physiotherapists

Abstract: Physiotherapy plays a fundamental role in managing adults with the joint hypermobility syndrome/Ehlers-Danlos syndrome hypermobility type (JHS/EDS-HT). However, it is a challenge for both the patient and the physiotherapist as the condition is poorly understood and treatment for JHS/EDS-HT is currently undefined. Insight into current practice is, therefore, necessary in order to establish baseline knowledge in this area and in the long term to improve the standard of patient care. Therefore, the purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…To date, the genetic basis of HEDS has not been elucidated and molecular diagnosis is not possible. HEDS patients may see multiple subspecialists without realizing a connection between their joint symptoms and multi-systemic involvement of the disease; they are often dismissed as hypochrondriacs, and report feelings of isolation from the lack of diagnosis49.…”
mentioning
confidence: 99%
“…To date, the genetic basis of HEDS has not been elucidated and molecular diagnosis is not possible. HEDS patients may see multiple subspecialists without realizing a connection between their joint symptoms and multi-systemic involvement of the disease; they are often dismissed as hypochrondriacs, and report feelings of isolation from the lack of diagnosis49.…”
mentioning
confidence: 99%
“…Despite its likely prevalence, there is poor understanding of the condition by physiotherapists and other health professionals (Rombaut et al, ). For example, 33.5% of Flemish physiotherapists reported having no idea about the impact of JHS on patients' lives (Rombaut et al, ) and 51% of UK physiotherapists reported having no training in hypermobility (Lyell, Simmonds, & Deane, ). When diagnosing JHS, physiotherapists most frequently used the Beighton score in conjunction with other assessment questions, with only 31% using the Brighton criteria (Palmer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…People with JHS present with such a wide array of signs and symptoms that they cannot be treated with one singular intervention (Malfait et al, ). Indeed, current treatment options include a very wide variety of pharmacological and non‐pharmacological interventions (Castori et al, ; Rombaut et al, ; Smith, Easton, et al, ). Evidence for the effectiveness of many interventions is either non‐existent or very limited (Castori et al, ; Engelbert et al, ; Palmer, Bailey, Barker, Barney, & Elliott, ; Smith, Easton, et al, ) but they are still frequently used (Rombaut et al, ), mainly based on clinical experience and patient feedback (Keer & Simmonds, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiotherapy is the mainstay of treatment for JHS (Palmer et al, ). However, few physiotherapists have received JHS‐specific training, and so they are unfamiliar with its presentation and lack confidence in its management (Lyell, Simmonds, & Deane, ; Palmer, Cramp, Lewis, Muhammad, & Clark, ; Rombaut et al, ). Physiotherapists also reported limited use of validated diagnostic and assessment tools (Palmer et al, ).…”
Section: Introductionmentioning
confidence: 99%